Developing “SEEY“ Android-Based Game for Learning English Grammar: Research and Development - Sari, Hesty Puspita; Maulidyah, Silvi Nuril; Aini, Miza Rahmatika (EDUCATIO : Journal of Education, 2022)
The study's goal is to create a “SEEY” android-based game for learning grammar with eighth-grade junior high school students. In this research, the research and development method is utilized (R and D). The study's emphasis was on 30 pupils from a random school in Blitar Regency, including six teachers and students from SMPN 1 Sutojayan, SMPN 1 Talun, and SMPN 1 Kanigoro. In addition to interviews, observations, and documents, this study also used a quantitative approach. the method of creating "SEEY" android-based game material as a teaching aid. Results of the study are displayed: (1) Developing “SEEY” android-based game for learning English grammar to eighth-graders in jun high school, with a focus on tenses that are more advanced and have four tenses (simple0present0tense, present0continuous0tense, simple0past0tense, and past0continuous tense) (2) “SEEY” android-based game was valid, as evidenced by the fact that media validators gave it an overall score of 271 and an 82 percent accuracy rate. This value falls between 81 and 100 percent according to the grading standards for the "Very Valid" Category. Additionally, the learning media “SEEY” android-based game is very appropriate for students to improve their Grammatical competence.